Pengaruh Ekstrak Jahe (Zingiber offcinale) Terhadap Kualitas Telur Asin - Astati Astati (Prosiding Seminar Biologi, 2018)
This study aims to identify the quality of the salty egg with  increasing  ginger extract (Zingiber officinale)  with different concentrated. This research used duck egg with increasing ginger with four treatment there are P0= 0 %,P1= 20 %, P2= 30 %, P3= 40 %, with every treatment that repeatedly four ways, where every repeatedly used five eggs samples the total of the samples is sixty eggs. Complete Random Device (RAL) by four treatments and four restatings. The parameter which is perceiving by the smell, egg yolk, taste, and sandy. Based on the results of the analysis of the variety and showed that the addition of ginger extract at different concentration did not give effect to the colour and fossil where the value (Fhit <Ftabel) at the concentration of 95% confidence and greatly affect the aroma and taste fossil where (Fhit> Ftabel) at 99% confidence concentration. The addition of ginger extract with a concentration of 40% gives a good influence.